Diagnosing the Integration of Resilient City Pillars and Indicators with Urban Energy Systems - Saleh, Aisha Alaa; Al-Mudares, Khalid Abdul Wahab (Al-Nahrain Journal for Engineering Sciences, 2022)
Contemporary urban discourse is paying increasing attention to the issue of urban resilience, due to the stresses, disasters and disturbances (natural and human) that the cities of the world are experiencing and facing, which confirms the need to be familiar with the concept of urban resilience, its dimensions, practices, and characteristics at different levels; In order to reach the aspects of developing the urban energy sector in them, and in a way that supports the preparedness of cities to face potential expected and unexpected disturbances in the future, as cities are usually formed from many main and sub-systems that are dynamically intertwined with each other, such as: the social and economic system, infrastructure systems, land use, and media Various transports, which have a high level of direct interactions with the natural environment; ; It is therefore necessary to understand how the city deals with the odds of threats and challenges in an integrated manner; To overcome its weaknesses and enhance its resilience of use, which aims to make cities more secure, resilient and sustainable in the future, as well as that requires rethinking the field of expanding the use of renewable energies and the general urban landscape. To become a search problem “Failure to exploit the potential of natural energies on the possibility of exploiting renewable natural energies with their components (active and passive) in the production of resilience urban formations in cities.” The aim of the research is to try to "extract an integrated theoretical framework on the characteristics of urban energy resilience from international and Arab experiences, and to diagnose its most important planning and design pillars and indicators, which can be adopted to evaluate the reality of urban energy resilience in local cities."The research hypothesized that “the exploitation of energy systems produced from renewable natural resources, for the purposes of environmental treatments for resilient cities, especially in the buildings of housing projects and their urban surroundings, reduces the consumption of fossil energies for the city, frees its sites from linking to depleted energy transmission networks, and reduces potential environmental pollution problems, which contributes to in the production of flexible energy systems and helps in the generation of flexible cities." The descriptive analysis method was adopted.